1979
DOI: 10.1111/j.1540-4560.1979.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Effects of Parental Divorce in Childhood on Adult Adjustment

Abstract: Relationships between experiencing a parental divorce or separation prior to age 16 and a variety of measures of adult adjustment and psychological functioning are examined using data from two national cross‐sectional surveys conducted nearly 20 years apart. Although few differences between adults from parentally‐divorced and intact family backgrounds persist when controls for contemporary life circumstances and other social background factors were included, two modest trends are still evident. First, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(76 citation statements)
references
References 26 publications
4
69
1
2
Order By: Relevance
“…These women had lower self-concepts and reported a greater sense of insecurity than did college women from intact families. A cross sectional study using national probability samples from 1957 and 1976 found longer lasting, although modest, effects (Kulka & Weingarten, 1979). Young adults (21-34 years old) who had experienced their parents' divorce before they were 16 were more likely to have gotten divorced themselves or to have never married.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These women had lower self-concepts and reported a greater sense of insecurity than did college women from intact families. A cross sectional study using national probability samples from 1957 and 1976 found longer lasting, although modest, effects (Kulka & Weingarten, 1979). Young adults (21-34 years old) who had experienced their parents' divorce before they were 16 were more likely to have gotten divorced themselves or to have never married.…”
mentioning
confidence: 99%
“…Slater, Stewart, & Linn, 1983). Furthermore, the 1953 sample was more negatively affected by divorce than was the 1976 sample (Kulka & Weingarten, 1979). Glenn (1985) pooled eight national surveys from 1973 to 1982 and found that men and women from divorced families, when compared to respondents from intact families, scored significantly lower on several measures of psychological well-being and were more likely to be divorced themselves.…”
mentioning
confidence: 99%
“…Kulka and Weingarten (1979) found that parental divorce had fewer negative effects on survey respondents interviewed in 1976 than it did for a comparable sample from 1957. Amato and Keith's (1991) meta-analysis of almost 100 studies found that the average negative effect of parental divorce on offspring wellbeing has weakened over time.…”
Section: Resultsmentioning
confidence: 99%
“…I ascertain whether the following affect trends in the probability of divorce transmission: race (Bumpass, Martin, and Sweet 1991;Glenn and Kramer 1987;McLanahan and Bumpass 1988), presence of siblings (Mueller and Pope 1977), Catholicism (McLanahan and Bumpass 1988), rural origins (Pope and Mueller 1976), age at marriage (Wolfinger 2003a(Wolfinger , 2005, and gender (Amato 1996;Glenn and Kramer 1987;Kulka and Weingarten 1979). Controlling for gender is especially important because men often fail to report their own divorces (Bumpass, Martin, and Sweet 1991).…”
Section: Analyses Include Continuous Variables Measuring Three Differmentioning
confidence: 99%
“…About one million children per year are intimately involved in the breakup of their parents marriage (U.S. Bureau of the Census, 1998). This experience has generally been considered a significant life event having stressful consequences for both the divorcing couple and their children (Bloom, Asher, & White, 1978;Fulton, 1979;Kukla & Weingarten, 1979 (Nielsen, 1999).…”
Section: B Divorce Statisticsmentioning
confidence: 99%